2018
DOI: 10.1021/jacs.8b05093
|View full text |Cite
|
Sign up to set email alerts
|

Bioorthogonal Removal of 3-Isocyanopropyl Groups Enables the Controlled Release of Fluorophores and Drugs in Vivo

Abstract: Dissociative bioorthogonal reactions allow for chemically controlling the release of bioactive agents and reporter probes. Here we describe 3-isocyanopropyl substituents as masking groups that can be effectively removed in biological systems. 3-Isocyanopropyl derivatives react with tetrazines to afford 3-oxopropyl groups that eliminate diverse functionalities. The study shows that the reaction is rapid and can liberate phenols and amines near-quantitatively under physiological conditions. The reaction is compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
168
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 112 publications
(170 citation statements)
references
References 48 publications
2
168
0
Order By: Relevance
“…In addition, the same group demonstrated that a pyrazole–imine intermediate (compound 79 in Scheme C) formed by tetrazine [1+4] cycloaddition with 3‐isocyanopropyl (ICP) tags ( 76 ) can undergo efficient payload release through imine hydrolysis and β‐elimination in aldehyde 80 . The feasibility of this “click and release” strategy was confirmed by the efficient activation of phenolic and carbamate drugs in live zebrafish …”
Section: When and Where: Linker Cleavage Promoted By External Stimulimentioning
confidence: 93%
“…In addition, the same group demonstrated that a pyrazole–imine intermediate (compound 79 in Scheme C) formed by tetrazine [1+4] cycloaddition with 3‐isocyanopropyl (ICP) tags ( 76 ) can undergo efficient payload release through imine hydrolysis and β‐elimination in aldehyde 80 . The feasibility of this “click and release” strategy was confirmed by the efficient activation of phenolic and carbamate drugs in live zebrafish …”
Section: When and Where: Linker Cleavage Promoted By External Stimulimentioning
confidence: 93%
“…Based on reports that 3‐oxopropyl groups liberated leaving groups by β‐elimination, we designed 3‐isocyanopropyl moieties that react with tetrazines to release payloads under physiological conditions (Scheme ). Effective release of phenols and amines from 3‐isocyanopropyl derivatives triggered by tetrazines was experimentally shown . 3‐Isocyanopropyl groups reacted with 3,6‐di(pyridin‐2‐yl)‐1,2,4,5‐tetrazine at rates of up to 4.0 m −1 s −1 in PBS/DMSO (90:10) at 37 °C.…”
Section: Reported Dissociative Bioorthogonal Reactionsmentioning
confidence: 99%
“…Albumin catalyzed the β‐elimination, and the release step went to completion in minutes. Isocyanopropyl‐modified molecules were easy to synthesize from inexpensive starting materials . Moreover, imaging and drug‐delivery experiments in zebrafish embryos demonstrated that the reaction is compatible with living systems.…”
Section: Reported Dissociative Bioorthogonal Reactionsmentioning
confidence: 99%
See 2 more Smart Citations